The Emerging Role of the IL-17B/IL-17RB Pathway in Cancer - Bastid, Jérémy; Dejou, Cécile; Docquier, Aurélie; Bonnefoy, Nathalie (Frontiers in Immunology, 2020)
Among inflammatory mediators, a growing body of evidence emphasizes the contribution of the interleukin 17 (IL-17) cytokine family in malignant diseases. Besides IL-17A, the prototypic member of the IL-17 family, several experimental findings strongly support the role of the IL-17B/IL-17 receptor B (IL-17RB) pathway in tumorigenesis and resistance to anticancer therapies. In mouse models, IL-17B signaling through IL-17RB directly promotes cancer cell survival, proliferation, and migration, and induces resistance to conventional chemotherapeutic agents. Importantly, recent work by our and other laboratories showed that IL-17B signaling dramatically alters the tumor microenvironment by promoting chemokine and cytokine secretion which foster tumor progression. Moreover, the finding that elevated IL-17B is associated with poor prognosis in patients with pancreatic, gastric, lung, and breast cancer strengthens the results obtained in pre-clinical studies and highlights its clinical relevance. Here, we review the current understanding on the IL-17B/IL-17RB expression patterns and biological activities in cancer and highlight issues that remain to be addressed to better characterize IL-17B and its receptor as potential targets for enhancing the effectiveness of the existing cancer therapies.